Copy number variation of c-c chemokine ligand 3-like 1 (CCL3L1), c-c chemokine receptor type 5 (CCR5) and CCR2 polymorphisms on the outcomes of antiretroviral therapy among Malaysian HIV patients - Mohamad Isa, Irma Izani (2020)
HIV/AIDS is a significant burden in Malaysia, affecting more than 90, 000 of the population. Several host genetic variations have been implicated in the pathogenesis of HIV infection, particularly on HIV susceptibility and disease progression to AIDS. These include CCR5 and CCL3L1, which encode for the CCR5 receptor and the ligand for the CCR5 receptor respectively. However, there is a noticeable discordancy in CD4 count recovery and viral load suppression between individuals during the highly active anti-retroviral therapy (HAART). However, the predictive value of these genetic variants on patients’ responses to the HAART is largely unknown. Therefore, the main objective of this study is to determine the impact of CCL3L1 copy number variation and selected CCR5/CCR2 polymorphisms on HIV susceptibility, CD4 count recovery and viral load suppression among Malaysian HIV patients during early HAART. Besides, the influence of socio-demographic and clinical factors is also considered. This cross-sectional study involved 182 HIV-positive patients of Malay, Chinese and Indian ethnicities who were attending out-patient clinics of three hospitals in Malaysia and 150 non-HIV (comparative) subjects. A subset of 170 HIV subjects who were receiving the standard first-line HAART regimen with available CD4 count and viral load data were selected for analyses on immunological and virological responses for up to 12 months after the initiation of HAART. Typing of CCL3L1 copy number used paralogue ratio test (PRT) followed by the copy number validation by microsatellites analyses. CCR5-Δ32 was genotyped by using PCR while both CCR5-R223Q and CCR2-V64I were identified by using PCR-restriction fragment length polymorphism (PCR-RFLP). Logistic regression was used to determine the effect of the predictors on achieving the target outcomes of CD4 count ≥500 cells/mm³ and viral load ≤50 copies/mL. Lower than average CCL3L1 copy number was associated with an increased risk of acquiring HIV-1 in Malay ethnic. Susceptibility to HIV was also reduced by having the mutant allele of CCR5-R223Q. In multivariable analysis after adjustment for socio-demographic and clinical factors, lower than average CCL3L1 copy number predicted a higher chance of CD4 recovery to ≥500 cells/mm³ at 8-12 months treatment with HAART. Furthermore, subjects with pre-treatment CD4 count ≥200 cells/mm³ were associated with at least five times more likely to achieve optimal CD4 recovery in the first 12 months of HAART. Besides, at 8-12 months of HAART, Chinese and Indian subjects were four and seven times respectively more likely to achieve CD4 count ≥500 cells/mm³ than Malay subjects. Viral load suppression to ≤50 copies/mL was not associated with the CCL3L1 copy number or CCR5/CCR2 genetic factors. Rather, the viral load suppression was negatively predicted by pre-treatment viral load ≥100,000 copies/mL and positively predicted by CD4 count ≥200 cells/mm³ in the first 4-6 months of HAART. In conclusion, both high CCL3L1 copy number and the mutant CCR5-R223Q are the potential factors that prevent HIV infection. The present study also highlights the contribution of low CCL3L1 copy number, ethnicity and early HAART initiation in order to achieve the optimal CD4 count recovery thus improving the management of HIV treatment.